Sexual minority tobacco use disparities across adolescence and the transition to young adulthood. (1st December 2020) - Krueger, Evan A.; Braymiller, Jessica L.; Barrington-Trimis, Jessica L.; Cho, Junhan; McConnell, Rob S.; Leventhal, Adam M.
Highlights: Sexual minority (SM) tobacco use disparities are concentrated among SM females. SM tobacco use disparities extend across several tobacco products. SM tobacco use disparities extend through both adolescence and young adulthood. The timing of SM tobacco use disparities varies by product type. Abstract: Introduction: Sexual minority (SM; e.g., lesbian, gay, bisexual) youth are disproportionately more likely to use tobacco than non-SM youth, yet there exist several critical gaps in knowledge. This study assessed (a) the timing of SM tobacco use disparities (e.g., during adolescence or early adulthood), (b) whether disparities generalize across different tobacco products, and (c) whether disparities differ by sex. Methods: Data were from a 6-year prospective cohort of diverse high school students from Southern California who were followed into early adulthood (9 waves, 2013–2019). SM (vs. non-SM) differences in past 6-month use were assessed for: any tobacco products, cigarettes, e-cigarettes, other products (e.g., hookah), and multiple products. Disparities were modeled longitudinally across adolescence (high school) and the transition to early adulthood (end of high school to post-high school). Differences were tested by sex. Results: Among females, SM disparities were evident for all outcomes during both adolescence and early adulthood; no differences were observed among males. For example, SM (vs. non-SM) females had higher odds of cigarette (aOR = 4.4 [3.0–6.5]) and e-cigarette (aOR = 1.7 [1.2–2.4]) use, averaged across adolescence. The timing of disparities varied by product. For example, cigarette use disparities emerged prior to high school and persisted through adolescence and young adulthood, while e-cigarette use disparities were present in early adolescence and young adulthood only. Conclusions: Young SM females are at especially high risk for tobacco use, across various tobacco products, throughout adolescence and young adulthood. Interventions must consider differences in the timing of disparities by product type.